Allosteric interactions between GABAB1 subunits control orthosteric binding sites occupancy within GABAB oligomers. (1st July 2018) - Stewart, Gregory D.; Comps-Agrar, Laëtitia; Nørskov-Lauritsen, Lenea Blanc; Pin, Jean-Philippe; Kniazeff, Julie
Abstract: The GABAB receptor was the first G protein-coupled receptor identified as an obligate heterodimer. It is composed of two subunits, GABAB1 containing the agonist binding site and GABAB2 responsible for G protein activation. The GABAB receptor was found to associate into larger complexes through GABAB1 -GABAB1 interactions, both in transfected cells and in brain membranes. Here we assessed the possible allosteric interactions between GABAB heterodimers by analyzing the effect of mutations located at the putative interface between the extracellular binding domains. These mutations decrease, but do not suppress, the Förster resonance energy transfer (FRET) signal measured between GABAB1 subunits. Further analysis of one of these mutations revealed an increase in G protein-coupling efficacy and in the maximal antagonist binding by approximately two-fold. Hypothesizing that a tetramer is an elementary unit within oligomers, additional FRET data using fluorescent ligands and tagged subunits suggest that adjacent binding sites within the GABAB oligomers are not simultaneously occupied. Our data show a strong negative effect between GABAB1 binding sites within GABAB oligomers. Accordingly, GABAB receptor assembly appears to limit receptor signaling to G proteins, a property that may offer novel regulatory mechanism for this important neuronal receptor. This article is part of the "Special Issue Dedicated to Norman G. Bowery". Graphical abstract: Image 1 Highlights: Oligomeric association of GABAB receptor is altered by mutations in GABAB1 VFT. Destabilization of GABAB VFT oligomeric interface increases coupling efficacy. The number of binding sites is increased by oligomer VFT interface destabilization. GABAB receptor oligomerization promotes a negative effect for ligand binding. Oligomerization of the GABAB receptor offers new way to modulate its signaling.